Last couple standing : a novel - Norman, Matthew, 1977- (Ballantine Books, 2020)
"The Core Four have been friends since college: four men, four women, four couples. They got married around the same time, had kids around the same time, and now, fifteen years later, they've started getting divorced around the same time, too. With three of the Core Four unions crumbling to dust around them, Jessica and Mitch Butler take a long, hard look at their own marriage. Can it be saved? Or is divorce, like some fortysomething zombie virus, simply inescapable? To maximize their chance at immunity, Jessica and Mitch try something radical. Their friends' divorces mostly had to do with sex--having it, not having it, wanting to have it with other people--so they decide to relax a few things. Terms are discussed, conditions are made, and together the Butlers embark on the great experiment of taking their otherwise happy, functional marriage and breaking some very serious rules. Jessica and Mitch are convinced they've hit upon the next evolution of marriage. But as lines are crossed and hot bartenders pursued, they each start to wonder if they've made a huge mistake. What follows is sexy, fun, painful, messy, and completely surprising to them both. Because sometimes doing something bad is the only way to get to the heart of what's really good"--